EMPLOYEE ENGAGEMENT AS MEDIATION OF KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE - Andini, Serly; Ekhsan, Muhamad (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This study aims to determine the contribution of knowledge management to employee performance by considering the mediating role of employee engagement. The population of this study were 420 employees and 91 people filled out the questionnaire. Sampling using the Slovin formula and 84 respondents were obtained. Data collection using an online questionnaire. Data were analyzed with SmartPLS. The results show that knowledge management has a contribution to employee engagement and employee performance. Employee engagement is also proven to mediate the effect of knowledge management on employee performance. This study concludes that knowledge management can improve employee performance through increased employee engagement. The findings of this research are anticipated to assist firms in developing more successful knowledge governance strategies by taking into account the vital function of staff commitment.